Effect of modified atmosphere packaging on shelf life and bacterial community of roast duck meat. (November 2020) - Chen, Xue; Zhao, Jiayue; Zhu, Lixian; Luo, Xin; Mao, Yanwei; Hopkins, David L.; Zhang, Yimin; Dong, Pengcheng
Graphical abstract: Highlights: MAP samples obtained higher redness, better sensory scores and lower lipid oxidation. CO-MAP samples exhibited the lowest TBARS values. CO2 -MAP were effectively retarded the spoilage bacteria growth. Roast duck bacterial dynamics was affected by the gas composition used in packages. Vibrio spp. was dominant in both 30% CO2 -MAP and CO-MAP at the end of storage. Abstract: The purpose of this work was to assess the effect of different packaging methods on the shelf life and bacterial communities of roast duck meat. Samples were packaged under the following five conditions: overwrapped packaging (OWP), 100% N2 (100% N2 -MAP), 30% CO2 /70% N2 (30% CO2 -MAP), 50% CO2 /50% N2 (50% CO2 -MAP), and 0.4% CO/30% CO2 /69.6% N2 (CO-MAP). Physicochemical and microbiological parameters were monitored during 14 days of chilled storage (0–4 °C). Results showed that MAP samples obtained higher and more stable redness, better sensory scores, and lower lipid oxidation, compared with OWP, in which CO-MAP samples had the lowest TBARS values (0.13–0.22 MDA/kg) during storage. Moreover, 30% CO2 -MAP, 50% CO2 -MAP, and CO-MAP effectively retarded the onset of bacterial spoilage and extended shelf life by 7 days compared with 100% N2 -MAP and OWP treatments. Additionally, bacterial succession was significantly affected by the gas composition used in the packages, especially the dominant biota at the end of storage, which played an important role in the spoilage of roast duck meat under specific packaging. On day 14, Pseudoalteromonas spp., Lactobacillus spp., and Pseudomonas spp. became the most predominate genera in OWP, 100% N2 -MAP, and 50% CO2 -MAP, respectively. Notably, Vibrio spp. was dominant in both 30% CO2 -MAP and CO-MAP, indicating 0.4% CO did not exert a further inhibitory effect on this genus. Additionally, the growth inhibition of Pseudoalteromonas spp., Lactobacillus spp., and Leuconostoc spp. by high CO2 concentration might be the reason for MAP (CO2 /N2 ) samples having lower levels of TVC. Globally, these results indicate that 30% CO2 -MAP, 50% CO2 -MAP, and CO-MAP are promising packaging methods to improve roast duck meat quality and achieve shelf life extension.